HUBUNGAN GAYA BELAJAR DAN MINAT BELAJAR DENGAN HASIL BELAJAR SENI RUPA SISWA KELAS VII SMP NEGERI 1 PADANG - AL MIRA FARRAS FADHILAH, Dr. Ramalis Hakim, M.Pd. (Serupa The Journal of Art Education, 2019)
The research carried out in SMP Negeri 1 Padang, especially class VII 2018/2019 on the subject of art and culture, aims to reveal the relationship: 1) Learning style with learning outcomes of fine art in class VII of SMP Negeri 1 padang, 2) Learning interest with learning outcomes of fine art in class VII of SMP Negeri 1 Padang, and 3) Learning style and learning interest of fine art in class VII of SMP Negeri 1 Padang. This research is a type of ex-post facto research with a correlational approach. The simple used was taken using the simple random sampling technique. Learning style and learning interest data are taken from questionnaire answers, then tested using product moment correlation and multiple correlation. The results of this study show that: 1) There is a significant relationship learning style with learning outcomes of fine art in class VII of SMP Negeri 1 Padang.Key Words: Learning Style, Learning Interest, Learning Outcomes.